Combined Alcohol and Energy Drink Use: Motivations as Predictors of Consumption Patterns, Risk of Alcohol Dependence, and Experience of Injury and Aggression. (20th May 2014) - Droste, Nicolas; Tonner, Lorraine; Zinkiewicz, Lucy; Pennay, Amy; Lubman, Dan I.; Miller, Peter
<x xml:space="preserve">Abstract</x> Background Coconsumption of alcohol with energy drinks (AED) is becoming increasingly popular among adolescents and young adults and has been associated with a range of harms. Motivations related to determined drunkenness and hedonistic drinking are potentially important in explaining both alcohol and AED consumption, given that a relationship has been identified between AED use and heavy alcohol consumption. This study aimed to explore motives for combined AED consumption, as well as their relationship with alcohol dependence and experiences of harm and aggression. Methods Students (n = 594) enrolled at Deakin University, Victoria, Australia, completed an anonymous online survey in 2012. Approximately two‐thirds of the sample (66.5%) were female, and the mean age was 22.3 (SD = 4.5), consistent with 2012 Deakin University enrollment. Results Principal axis factor analysis of 14 items measuring motivations for AED use identified 4 factors, categorized as "hedonistic, " "social, " "energy/endurance, " and "intoxication–reduction" motives. Multinomial and binary logistic regression analyses demonstrated that hedonistic motives for AED use significantly predicted increases in alcohol and energy drink coconsumption during AED episodes, risk of alcohol dependence, as well as experiencing harm and aggression. Intoxication–reduction motives significantly predicted harm outcomes. Conclusions Hedonistic motives specific to sensation and pleasure ideals are implicated in negative consequences associated with coconsumption of alcohol and energy drinks. Further, consumers who reported using AEDs to reduce alcohol intoxication were at increased risk of negative outcomes, a finding indicating that consumer knowledge of the effects of AED use may be limited.